Fatigue properties of UFG Ti grade 2 dental implant vs. conventionally tested smooth specimens - Fintová, Stanislava; Dlhý, Pavol; Mertová, Kateřina; Chlup, Zdeněk; Duchek, Michal; Procházka, Radek; Hutař, Pavel (Journal of the mechanical behavior of biomedical materials, 2021)
Complicated geometry in combination with surface treatment strongly deteriorates fatigue resistance of metallic dental implants. Mechanical properties of pure Ti grade 2, usually used for dental implant production, were shown to be significantly improved due to intensive grain refinement via Conform SPD. The increase of the tensile strength properties was accompanied by a significant increase in the fatigue resistance and fatigue endurance limit. However, the SLA treatment usually used for the implants' surface roughening, resulted in the fatigue properties and endurance limit decrease, while this effect was more pronounced for the ultrafine-grained comparing to the coarse-grained material when tested under tensile-tensile loading mode. The testing of the implants is usually provided under the bending mode. Even though different testing condition for the conventional specimens tests and implants testing was adopted, a numerical study revealed their comparable fatigue properties. The fatigue limit determined for the implants was 105% higher than the one for coarse-grained and only by 4 % lower than the one for ultrafine-grained Ti grade 2. Based on the obtained results, conventional specimens testing can be used for the prediction of the fatigue limit of the implants.
Keywords: Fatigue; Ultrafine-grained; testování materiálů; pevnost v tahu; Dental implant; Surface Properties; povrchové vlastnosti; Dental Implants; Titanium; Tensile Strength; Ti grade 2; zubní implantáty; SLA treatment; titan; Materials Testing